Prediction of Vehicle Fuel Consumption Model Based on Artificial Neural Network - Noraziah, Ahmad; Mohd Azhar, Mohd Amer; Abdalla, Ahmed N.; Ainul Azila, Che Fauzi (Trans Tech Publications, Switzerland, 2014)
With the increasing cost of fuel price minimizing fuel consumption is a major concern as far as sustainable engineering is concerned It is apparent that effective techniques for estimating fuel consumption costs are essential in order to avoid unnecessary fuel wastage and make use the most out of it In this paper an Artificial Neural Network (ANN) 2approach is used to fuel consumption model was proposed First few estimation calculator techniques have2 been briefly described Second the proposed optimization objective is to minimize the travel distance which is the corresponding to vehicle 2routing problem The neural network model has 5 input nodes at layer first which are representing engine size distance fuel type speed and passenger 15 nodes at hidden layer and one output node representing the fuel consumption costs. Finally calculations results are compared with other fuel model which indicate that estimation of fuel cost can be more accurate to optimize the fuel consumption usage accurate to optimize the fuel consumption usage.